Evaluación de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en parroquias de Pujilí. - Naranjo Guilcaso, Kevin Francisco (2024)
The Technical University of Cotopaxi, through the Veterinary Medicine Department, has proposed the sustainable genetic improvement project in cattle in the Cotopaxi province, focusing on evaluating traits in cattle to increase the profitability of milk production, especially for small-scale producers in the Pujilí canton. In the parishes of Pujilí, the genetic improvement project was carried out with the participation of 307 cattle from 72 producers. It began with weighing the animals for the administration of dewormers and vitamins, contributing to the fertility and health of the livestock. Females prepared for reproduction were selected, and gynecological check-ups and proper management against reproductive diseases were performed. Subsequently, females ready for artificial insemination were selected. Additionally, the breeds of the cattle were identified. Among the identified breeds are: 69.71% Holstein, 6.84% Crossbred Holstein, 4.23% Red Holstein, 3.91% Jersey, 4.98% F1 and Normande, 1.95% Brown Swiss and Montbéliarde, 1.30% Gyrolando, 0.65% Brahman, and 0.33% Red Crossbred Holstein, Charolais, Brahman, and Ayrshire. An analysis of different characteristics such as animal weight and milk production evaluation as density using a lactodensimeter was conducted. In November, an average of 1,027 g/l was recorded, while in December, it was 1,032 g/l. For milk weight, an average of 8.48 kg/day was obtained in November, while in December, it was 8.24 kg/day. In the mastitis test conducted in November, 85.19% were negative, 5.56% were slightly positive, and 9.22% showed traces. In November, mastitis negativity reached 90.74%, and no slightly positive cases were observed. Traces were present in 9.26% of cases. In milk production in Pujilí, an average weight of 8.36 kg was recorded over two months. The milk density increased from 0.004 g/l in November to a higher value in December. There was an improvement in the mastitis test, although there was a slight increase of 0.04% in trace presence. Additionally, as part of the project, 5 Holstein cattle were selected and prepared for genetic improvement. It is suggested to expand the genetic improvement initiative to other sectors of the Pujilí parishes through informational exhibitions based on the project, with the participation of producers and community leaders.